(untitled) (Asian Journal of Pharmaceutics (AJP), 2021)
Objective: This study evaluated the perceptions of infectious diseases among tourists about risk categories of different diseases. Materials and Methods: A cross-sectional study using a self-developed research instrument was designed and used to collect data from the tourists visiting Penang, Malaysia. Descriptive, comparative, and inferential statistics were performed using Statistical Package for the Social Sciences. Results: One-half of the respondents perceived hepatitis A (50.3%), meningitis (52.3%), and typhoid fever (51.3%) as low-risk diseases, while about 37% and 33% tourists considered dengue and HIV/AIDS as high-risk diseases, respectively. Conclusion: The results suggest that tourists perceived varied risk levels of infectious diseases in Malaysia, indicating that the tourists should take proper preventive measures to avoid contracting these diseases.